A study of the knowledge and skills requirements for the humanities librarian in supporting postgraduate students - Johnson, Glynnis (Library and Information Studies Centre (LISC), 2017)
This study sought to develop a knowledge and skills framework for humanities librarians supporting postgraduate students against which such librarians may 'measure' their current knowledge and skills; as well as ascertain areas for new skills acquisition. This objective was supported by five critical questions which attempted to elicit data from the literature reviewed, humanities librarians interviewed and postgraduate student respondents. A constructivist qualitative approach with a multiple case study design was employed by the study. Core Competency Theory was used to provide theoretical support. Empirical data was collected by conducting interviews and focus group discussions with purposively sampled humanities librarians and postgraduate students at three selected higher education institutions in the Western Cape, namely, Stellenbosch University, University of Cape Town and the University of the Western Cape. Collected data were analysed using NVivo 11 Pro (for coding purposes) and thematic content analysis by the researcher. An important conclusion of the study, inter alia, based on its findings and discussion in the context of the literature reviewed and theory supporting the study, is that a combination of discipline-specific knowledge and skills, generic skills and personal attributes are required by humanities librarians in order to effectively support postgraduate students especially in the current digital age. The study also concludes that while subject knowledge is required, expert knowledge of humanities subjects is not generally necessary in order to provide support to postgraduate students. Rather, a broad working knowledge of a subject is required. However there are exceptions in the case of highly specialised subjects such as Music. The study recommends that both continuing professional development for humanities librarians supporting postgraduate students, amongst other librarians, as well as LIS schools in their curriculum design and development for LIS professionals entering the academic library environment, take into account a combination of discipline-specific knowledge and skills, generic skills and personal attributes for effective delivery of academic library services. To this end the study presents a knowledge and skills framework which humanities librarians supporting postgraduate students may use to 'measure' their current knowledge and skills as well as to ascertain areas for new knowledge and skills acquisition.